A TRANSLATION ANALYSIS OF IDIOMATIC EXPRESSIONS IN A SERIES OF UNFORTUNATE EVENTS: THE END, A NOVEL WRITTEN BY LEMONY SNICKET - Eulis Nur Diani, - (2010)
ABSTRACT This study is entitled A TRANSLATION ANALYSIS OF IDIOMATIC expressionS IN A SERIES OF UNFORTUNATE EVENTS: THE END, A NOVEL WRITTEN BY LEMONY SNICKET. The aims of the study are to find out the types of idiomatic expressions which are mostly used in the novel, the procedures of translation employed by the translator in translating the idiomatic expressions and the quality of the translation. This study is a qualitative case method especially a textual analysis. This method allows the writer to make a systematic and factual description of the obtained data. The data were all the idiomatic expressions discovered in the novel. The results of the research indicate that there were three types of idiomatic expressions discovered in the novel. These types of idiomatic expressions were categorized based on Makkai (1972). Those were 245 idiomatic expressions which comprise lexemic idioms (189 items), phraseological idioms (37 items), and saying or proverbs (19 items). Lexemic idioms is the type of idiom that is frequently discovered in the novel. Several procedures were applied by translator in translating idiomatic expressions. The translation procedure was offered by Vinay and Darbelnet (2000), Newmark (1988, 1991) and Harvey (2000). And these procedures were consisted of literal (12 items), cultural equivalent (9 items), through-translation (13 items), shift or transposition (2 items), equivalence (166 items), reduction (40 items), and couplet (3 items). Equivalence translation procedure is the most frequent procedure used in translating the idiom discovered in the novel. Moreover, the quality of the translation is generally acceptable, understandable and suitable despite some translations which are unnatural. Most of the translations fulfill the criteria of a good translation such as easily understood, preserve the original text's character of the style and manner and should read like an original and should not read like a translation. This study also covers the translation assessment proposed by Barnwell cited in Larson (1984), in terms of clarity, accuracy and naturalness and carries out the equivalent theory (Nida 1971) and skopos theory (Vermeer 1989). Those criterias can be useful for the translators in making a qualified translation, especially in translatinng idiomatic expressions. It is recommended that further study be conducted to look more closely at the quality of translation of other texts.